Effects of Injection Rate Profile on Combustion Process and Emissions in a Diesel Engine - Fuqiang Bai; Zuowei Zhang; Yongchen Du; Fan Zhang; Zhijun Peng (Journal of Combustion)
When multi-injection is implemented in diesel engine via high pressure common rail injection system, changed interval between injection pulses can induce variation of injection rate profile for sequential injection pulse, though other control parameters are the same. Variations of injection rate shape which influence the air-fuel mixing and combustion process will be important for designing injection strategy. In this research, CFD numerical simulations using KIVA-3V were conducted for examining the effects of injection rate shape on diesel combustion and emissions. After the model was validated by experimental results, five different shapes (including rectangle, slope, triangle, trapezoid, and wedge) of injection rate profiles were investigated. Modeling results demonstrate that injection rate shape can have obvious influence on heat release process and heat release traces which cause different combustion process and emissions. It is observed that the baseline, rectangle (flat), shape of injection rate can have better balance between NOx and soot emissions than the other investigated shapes. As wedge shape brings about the lowest NOx emissions due to retarded heat release, it produces the highest soot emissions among the five shapes. Trapezoid shape has the lowest soot emissions, while its NOx is not the highest one. The highest NOx emissions were produced by triangle shape due to higher peak injection rate.